Transmission of digital data over a rayleigh fading channel - Karim, M.R. (Institute of Electrical and Electronics Engineers (IEEE), 1982)
In a microwave mobile telecommunications system, a digital message must be transmitted several times to overcome the effects of Rayleigh fades that characterize this channel, and thus ensure a high probability that the message is received error-free. An analytic approach to an evaluation of the comparative performance of different transmission schemes in terms of the probability of a transmission failure is presented, and a basis for the design of an efficient scheme is provided. Some fade statistics that have been used are presented. The upper bounds are derived on probability of the transmission failure for three different schemes. The actual failure rates as determined in an experimental simulation are then shown for those schemes that the theoretical study predicts to be acceptable. It is shown that an efficient scheme for the Rayleigh fading channel is the block-protected one in which a message is transmitted four times, each transmission 4-ms long and spaced 4-ms apart. The spacing is obtained by interleaving a similar transmission of another message. The receiver discards a transmission if it fails the parity checks.